Light Intensity Alters the Behavior of Monilinia spp. in vitro and the Disease Development on Stone Fruit-Pathogen Interaction - Balsells-Llauradó, Marta; Torres, Rosario; Vall-llaura, Núria; Casals, Carla; Teixidó, Neus; Usall, Josep (Frontiers in Plant Science, 2021)
The development of brown rot caused by the necrotrophic fungi Monilinia spp. in stone fruit under field and postharvest conditions depends, among others, on environmental factors. The effect of temperature and humidity are well studied but there is little information on the role of light in disease development. Herein, we studied the effect of two lighting treatments and a control condition (darkness) on: (i) several growth parameters of two Monilinia spp. (M. laxa and M. fructicola) grown in vitro and (ii) the light effect in their capacity to rot the fruit (nectarines) when exposed to the different lighting treatments. We also assessed the effect of such abiotic factors in the development of the disease on inoculated nectarines during postharvest storage. Evaluations also included testing the effect of fruit bagging on disease development as well as on ethylene production. Under in vitro conditions, lighting treatments altered colony morphology and conidiation of M. laxa but this effect was less acute in M. fructicola. Such light-induced changes under in vitro development also altered the capacity of M. laxa and M. fructicola to infect nectarines, with M. laxa becoming less virulent. The performance of Monilinia spp. exposed to treatments was also determined in vivo by inoculating four bagged or unbagged nectarine cultivars, indicating an impaired disease progression. Incidence and lesion diameter of fruit exposed to the different lighting treatments during postharvest showed that the effect of the light was intrinsic to the nectarine cultivar but also Monilinia spp. dependent. While lighting treatments reduced M. laxa incidence, they enhanced M. fructicola development. Preharvest conditions such as fruit bagging also impaired the ethylene production of inoculated fruit, which was mainly altered by M. laxa and M. fructicola, while the bag and light effects were meaningless. Thus, we provide several indications of how lighting treatments significantly alter Monilinia spp. behavior both in vitro and during the interaction with stone fruit. This study highlights the importance of modulating the lighting environment as a potential strategy to minimize brown rot development on stone fruit and to extent the shelf-life period of fruit in postharvest, market, and consumer’s house.